(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The facial nerve should be sacrificed only if there is strong indication. Sometimes it is possible to sacrifice only part of the facial nerve and this termed "semiconservative parotidectomy". The commonest operation performed is superficial conservative parotidectomy, which is removal of the parotid superficial to the facial nerve with nerve preservation. A total conservative parotidectomy was performed only if clearly indicated by the pathological condition, since the complete freeing of the facial nerve in this operation increases the incidence of nerve paralysis. Objective:To demonstrate under what circumstances is the surgeon likely to be called upon to sacrifice the facial nerve deliberately, and mentioning what be done to reduce the risk of functional facial paralysis following conservative parotidectomy. Methods:The material comprises 30 cases of parotidectomy of all types. We analysed the incidence and degree of functional facial paralysis following conservative parotidectomy and also we reported some experimental work attempting to elucidate its etiology. We classify the degree of facial nerve paralysis to grade I, absent or slight, grade II moderate, grade III complete. Results:We did superficial parotidectomies for 22 cases, 19 had grade I, two had grade II and only one had grade III facial nerve paralysis. Conservative total parotidectomies done for 2 cases, one had grade I and one had grade III facial nerve paralysis. Semiconservative parotidectomies done for 4 cases all had grade I facial nerve paralysis and lastly radical parotidectomies done for 2 cases, the results had grade III for two cases facial nerve paralysis. Conclusion:To reduce the incidence of facial paralysis after conservative parotidectomy: carrying total parotidectomy only when clearly demanded by pathological condition by avoiding washing out the wound, and by measures designed to preserve the blood supply of the trunk of the facial nerve. The present study support that ischemia is the principal factor in post-parotidectomy functional facial paralysis. Key words: Parotidectomy, Facial nerve, Mixed tumor